2019
DOI: 10.1038/s41598-018-37896-7
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of dictyostelid cellular slime molds in high-elevation habitats on the Qinghai-Tibet Plateau, China

Abstract: Dictyostelid cellular slime molds (dictyostelids) are key components of soil microbes. The Qinghai-Tibet Plateau is characterized by unique and important forest types because of the considerable range in elevation which exists. During the period of 2012, 2013 and 2016, 12 species of dictyostelids were yielded from samples collected in this region, including two new species and three new records for China. Six other species were new records for this region. Ontogeny, morphology, ultrastructure and systematic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Contradictory results were reported when development of antibodies to IDUA were examined. In some cases post-transplant ERT was associated with the development of IDUA antibodies, which were inhibitory and were accompanied with an increase in heparan sulfate excretion [ 67 , 69 ] and poorer endurance as established by the 6-min-walk-test [ 67 ]. However, in the absence of inhibitory antibodies, ERT post-HSCT had a beneficial effect on the 6-min walk test [ 67 ].…”
Section: Standard Therapies For Mps Imentioning
confidence: 99%
“…Contradictory results were reported when development of antibodies to IDUA were examined. In some cases post-transplant ERT was associated with the development of IDUA antibodies, which were inhibitory and were accompanied with an increase in heparan sulfate excretion [ 67 , 69 ] and poorer endurance as established by the 6-min-walk-test [ 67 ]. However, in the absence of inhibitory antibodies, ERT post-HSCT had a beneficial effect on the 6-min walk test [ 67 ].…”
Section: Standard Therapies For Mps Imentioning
confidence: 99%
“…Tang et al ( 24 ) indicated that elevation, rather than vegetation, is the primary predictor of rhizosphere microbial community structure in areas of alpine tundra on Changbai Mountain. Liu et al ( 25 ) reported that at higher elevations on the Qinghai–Tibet Plateau, dictyostelids appear to be relatively common. As such, in the present study soil samples were collected over a wide range of elevations (675 to 2,636 m) to obtain new isolates of dictyostelids and to determine their patterns of diversity at high elevations on Changbai Mountain.…”
Section: Introductionmentioning
confidence: 99%
“…Islet viability was measured in duplicate using acridine orange (AO) and propidium iodide (PI) staining on day 1 of culture following established protocols. 27 Islet viability was significantly different between Collagenase P (82.7 ± 1.3%), Collagenase AF‐1 GMP grade (89.3 ± 1.21%), but we observed no significant difference in Collagenase AF‐1 GMP grade with Liberase MTF C/T GMP grade islet isolations (85.3 ± 3.42%) (Table 2 )( P > .05).…”
Section: Resultsmentioning
confidence: 57%
“…The islets were counted using an islet number and islet equivalent number (IEQ) after staining with DTZ (Sigma‐Aldrich). 27 Islet sizes were determined by calculating the average size of islets. Islet viability after 24‐hour culture was measured using double‐florescence staining with acridine orange (Sigma)/propidium iodide (Sigma) for 30 minutes: islet viability: 100% ‐ (dead islet cells/total islet cells × 100%).…”
Section: Methodsmentioning
confidence: 99%